HUBUNGAN ANTARA AKTIVITAS BELAJAR KELOMPOK DENGAN INDEKS PRESTASI MAHASISWA SEMESTER 6 FAKULTAS KEDOKTERAN UNIVERSITAS HANG TUAH SURABAYA TAHUN AJARAN 2017/2018 - Handajani, Fitri; Hapsari, Kinanti; Garianto, Efyluk (UNUSA Press, 2019)
One of the active learning methods is to do a study group. Researcher is interested in research on the correlation between study group activities and student’s grade, so that students can find learning methods which may influence academic outcomes and facilitate learning, especially the medical students. This observational analytic study was carried out with a cross sectional design. The data of this study were obtained from the answers to the respondent's questionnaire in the Medical Faculty of Hang Tuah University, Surabaya. The sample in this study were semester 6 students of the 2017/2018 academic year at the Faculty of Medicine, University of Hang Tuah Surabaya (130 respondents). Based on the Spearman correlation statistical test between study group activities with the 6th semester students grade point, the significance of the correlation between study group activities and the 6th semester students grade point is 0.687. With a value of α = 0.05, means p> α, it can be concluded that the correlation between the two variables is not significant so that H0 accepts and H1 is rejected. So, there is no correlation between study group activities with 6th semester grade point. There is no correlation between study group activities and the 6th semester students grade point in the Faculty of Medicine, Hang Tuah University Surabaya.